2016
DOI: 10.1200/jco.2016.67.7450
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-Related Fatigue in Patients With and Survivors of Hodgkin Lymphoma: The Impact on Treatment Outcome and Social Reintegration

Abstract: Purpose Cancer-related fatigue occurs frequently in patients with Hodgkin lymphoma (HL) and has a major impact on their quality of life. We hypothesized that severe fatigue (sFA) might have an impact on patients' treatment outcome and social reintegration. Methods Of 5,306 patients enrolled in the German Hodgkin Study Group's fifth generation of clinical trials in HL (HD13, HD14, and HD15; nonqualified and older [> 60 years] patients excluded), 4,529 provided data on health-related quality of life. We describe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
0
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(62 citation statements)
references
References 27 publications
2
54
0
6
Order By: Relevance
“…Thirty‐seven percent of our patients reported the feeling of considerable and persistent fatigue (Table ). This is in line with previous studies where fatigue has been identified as a major residual complaint following recovery from HL and the effects of therapy (Straus, ; Behringer et al , ). Remarkably, in our study, the subjective experience of fatigue has not been associated with the objectively measured neurocognitive performance, suggesting that the cognitive impairment, experienced by about 40% of study participants, cannot be attributed to fatigue.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Thirty‐seven percent of our patients reported the feeling of considerable and persistent fatigue (Table ). This is in line with previous studies where fatigue has been identified as a major residual complaint following recovery from HL and the effects of therapy (Straus, ; Behringer et al , ). Remarkably, in our study, the subjective experience of fatigue has not been associated with the objectively measured neurocognitive performance, suggesting that the cognitive impairment, experienced by about 40% of study participants, cannot be attributed to fatigue.…”
Section: Discussionsupporting
confidence: 92%
“…The young patient age and improved prognosis result in a continuously growing population of HLS, who are at risk of long‐term chemo/radio therapy toxicity (Straus, ). Frequent complaints among HLS include persistent fatigue and changes in cognitive functions (Joly et al , ; Krull et al , ; Behringer et al , ). Cancer‐related cognitive impairment (CRCI) is a commonly reported adverse effect of various malignancies and their therapies among adult survivors (Wefel et al , ).…”
mentioning
confidence: 99%
“…Survivorship programs are focusing more on screening for serious late toxicities in HL, such as secondary breast cancer and lung cancer 37,38 and cardiovascular disease, as well as the impact on quality of life (eg, the impact of fatigue and sexual dysfunction). 39,40 Our data support the concept that rational cHL survivorship programs should focus mainly on appropriate management of late toxicities rather than on screening for preclinical relapse in patients in complete remission. In particular, actively screening for relapse after EFS24 does not seem cost effective, because 5-year relapse risk is reduced to less than 5% for nearly all young patients with cHL.…”
Section: Discussionsupporting
confidence: 66%
“…A longitudinal prospective evaluation of HRQoL in adults with HL enrolled on therapeutic trials noted severe levels of fatigue was common prior to the start of chemotherapy, and differed significantly by disease stage, whereas persistent fatigue in survivors did not correlate with level of therapy intensity (Kreissl et al , ). While severe fatigue at baseline was associated with a risk of poorer PFS, this effect was abrogated in the patients randomized to escalated therapy for any given group (Behringer et al , ).…”
Section: Primary Prevention To Close the Survivorship Gapmentioning
confidence: 99%